1998
DOI: 10.1046/j.1365-2141.1998.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult biphenotypic acute leukaemia: an entity with poor prognosis which is related to unfavourable cytogenetics and P‐glycoprotein over‐expression

Abstract: Summary. Biphenotypic acute leukaemia (BAL) patients represented 8% of the 287 de novo consecutive adult acute leukaemias (23 BAL, 230 acute myeloid leukaemia (AML) and 34 acute lymphoblastic leukaemia (ALL)) referred to our department during the last 4-year period. Of these 23 BAL patients, 14 patients showed myeloid morphology and nine cases lymphoid morphology according to FAB criteria. There were no differences between lymphoid and myeloid BAL according to clinical and biological presentation and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
114
6
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(138 citation statements)
references
References 38 publications
16
114
6
2
Order By: Relevance
“…Table 1 Primers sequence for molecular analysis (4)(q23)x2,der(4;7) (p10;q10),+t(4;7)(q12;q32), add(6)(p25)x2, +del(6)(q12),add(7)(q11.2),del(7)(p13), +der (7) Our data are similar to previously reported series 9,14,15 ( Table 4). The theory that the cell of origin in BAL is an early hematopoeitic stem cell, is supported by nearly all cases of BAL in our study expressing stem cell marker CD34.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Table 1 Primers sequence for molecular analysis (4)(q23)x2,der(4;7) (p10;q10),+t(4;7)(q12;q32), add(6)(p25)x2, +del(6)(q12),add(7)(q11.2),del(7)(p13), +der (7) Our data are similar to previously reported series 9,14,15 ( Table 4). The theory that the cell of origin in BAL is an early hematopoeitic stem cell, is supported by nearly all cases of BAL in our study expressing stem cell marker CD34.…”
Section: Discussionsupporting
confidence: 89%
“…Few studies have analyzed the diagnostic and prognostic factors, clinical and biological presentation of BAL patients when compared to other ALs. 5,6,[9][10][11] Herein we have utilized morphological, immunophenotypic, cytogenetic and molecular genetic characteristics to assess whether the EGIL scoring system is sufficiently robust, in practice, to define BAL.…”
Section: Introductionmentioning
confidence: 99%
“…Additional abnormalities included deletion of 6q, 5q and 12p. 35 Similar genetic findings were noted by Legrand et al 40 in their study of 23 biphenotypic acute leukemias. These authors also looked at MDR1 gene expression and found that it was higher in patients with biphenotypic acute leukemia than AML using RT-PCR and flow cytometry.…”
Section: Genetic Findingssupporting
confidence: 79%
“…Similarly, Xue et al 36 found that adult patients with biphenotypic leukemia had a worse overall survival and disease-free survival than those with either AML or ALL. Legrand et al 40 also found that adult patients with biphenotypic acute leukemia had a worse prognosis in terms of achieving complete remission and 4-year overall survival when compared with AML or ALL patients. Pediatric cases of biphenotypic acute leukemia have been found to have better prognosis when compared with adult biphenotypic cases.…”
Section: Clinical Outcomementioning
confidence: 96%
“…Anti-apoptosis mechanisms, alterations of tumor suppressor genes, altered immunogenicity, and drug-resistance mechanisms act in combination [39]. AMLL exhibits strong resistance against chemotherapy, resulting in poor patient prognosis [40,41]. In the present study, expression levels of IAPs in AMLL blasts were higher than those in control samples.…”
Section: Discussionmentioning
confidence: 40%